Survey of Adolescents' and Emerging Adults' Preferences for Gonorrhea and Chlamydia Testing in Primary Care. Issue 5 (13th May 2023) - Reingold, Sarah; Tomcho, Margaret; Thomas-Gale, Tara; Haynes, Christine; O'Leary, Sonja; Warsh, Sarah; Rinehart, Deborah; Frost, Holly
Abstract : A study of adolescents and emerging adults in Denver, Colorado, found that participants preferred opt-out gonorrhea and chlamydia testing compared with risk-based testing. Abstract: Our study assessed adolescents' and emerging adults' (ages 14–24 years) preferences for opt-out gonorrhea and chlamydia screening compared with risk-based screening. Most participants (93%) preferred opt-out gonorrhea and chlamydia testing compared with risk-based testing (6%), and opt-out testing was associated with less sexually transmitted infection–related stigma ( P < 0.05).